35 Competency Based Talent Management (CBTM) programme graduands celebrated by UMP Advanced - Mimi Rabita, Abdul Wahit (UMPSA, 2022)
KUANTAN, 7 September 2022 - A total of 35 graduands of the Competency Based Talent Management (CBTM) Programme were celebrated in a programme organised by UMP Advanced at the AC Marriot Hotel.